CYTOGENETIC AND BIOTECHNOLOGICAL ASSESSMENT OF STALLIONS OF TRAKEN AND HANNOVER STUD BREEDS - Ткачова, О. Л.; Добродєєва, Л. Т.; Россоха, Л. В.; Россоха, В. І.; Ткачов, О. В. (Scientific Progress & Innovations, 2013)
The comparative citogenetic and biotechnological evaluation of the inspected Traken and Hannover stallions by their general chromosomal instability and by the quantitative and qualitative parameters of sperm after thawing have been conducted. The general chromosomal instability of the investigated stallions of Hannover breed was 4,9%, the biotechnological fitness of sperm was 76,19% and the biotechnological fitness of sperm in the stallions of Traken breed was 72,73 and their chromosomal instability was 5,91%. The presence of pair and circular aberrations also influences the biotechnological fitness of sperm of the inspected stallion.